1995
DOI: 10.1111/j.1439-0523.1995.tb00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selection and opportunities for recombination in doubled‐haploid populations of barley (Hordeum vulgare L.)

Abstract: Doubled-haploid breeding systems are typically based on sampling gametes from F, plants. However, in the case of repulsion linkages, additional recombination could be advantageous. Pre-selection of gamete donors might also shift progeny performance in a desired direction. The objectives of this study were to quantify the effects of an additional round of recombination and assess the effectiveness of preanthesis selection in the production of barley doubled haploids. Assessments were conducted on: 1. 100 F,-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Similarly, Snape and Simpson (1981) inclined to produce DHs from F 2 generation in barley by comparing the gain in genetic variation for 6 agronomic traits with DH lines derived from F 1 , F 2 , F 3 and intermated F 2 (S3) generations [37]. In contrast, Iyamabo and Hayes (1995) did not found more favorable genotypes in DH lines produced from F 2 generation than that from F 1 generation in barley, therefore, they preferred to use F 1 generation for producing DHs [38]. In present study, the overall breeding efficiency of producing DHs from filial generations was in the order of F 2 >F 3 >F 1 , indication F 2 generation is better for producing DHs in breeding efficiency, which confirmed the majority results above.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Snape and Simpson (1981) inclined to produce DHs from F 2 generation in barley by comparing the gain in genetic variation for 6 agronomic traits with DH lines derived from F 1 , F 2 , F 3 and intermated F 2 (S3) generations [37]. In contrast, Iyamabo and Hayes (1995) did not found more favorable genotypes in DH lines produced from F 2 generation than that from F 1 generation in barley, therefore, they preferred to use F 1 generation for producing DHs [38]. In present study, the overall breeding efficiency of producing DHs from filial generations was in the order of F 2 >F 3 >F 1 , indication F 2 generation is better for producing DHs in breeding efficiency, which confirmed the majority results above.…”
Section: Discussionmentioning
confidence: 99%
“…Plots were spaced 30 cm apart and the seeding rate was 10 seeds per hill. The results of the complete experiment, in terms of population performance, were presented by Iyamabo and Hayes (1994). For the purposes of this study, only data from the 100 Fpderived lines were used.…”
Section: Methodsmentioning
confidence: 99%
“…Caligari and Powell (1985) found that DH system gave an accurate univariate cross prediction, but multivariate cross prediction based on F 3 families had a more accurate ranking of crosses than the DH system in barley breeding. Selecting the gamete donors may also shift the offspring performance in a desired direction, while postponing the generation for deriving DH should be weighed against any delays and additional costs (Iyamabo and Hayes, 1995). Bernardo (2009) argues that DHs in maize -an outcrossing species-should be induced from F 2 instead of F 1 plants because such an approach does not delay inbred development, particularly if using a year-round nursery to get new F 1 s on a speculative basis.…”
Section: Genetic Gains Through Haploid Breeding Vis-à-vis Other Crossmentioning
confidence: 99%